Pengembangan Sistem Pelayanan Surat Menyurat dan Pengaduan Layanan Berbasis Website di Desa Srirahayu Menggunakan Metode Waterfall dan Framework Laravel - Ilham, Mochammad Ilham Faadhilah; Ifani Hariyanti (STIKes Ibnu Sina Ajibarang, 2025)
Administrative services for correspondence and public complaints in villages are still largely handled manually, resulting in challenges in efficiency, speed of service, and poorly documented records. These issues are crucial to address to ensure better organized and responsive public services at the village level. This study aims to develop a website-based correspondence and complaint system accessible to the public and village officials. This study utilizes the Laravel Framework and Waterfall system development techniques. The results demonstrate that the system successfully simplifies the digital submission process for letters and complaints, and assists village officials in verifying and documenting data more efficiently. Based on implementation and testing, the system is considered effective and feasible to use, even though it is still operating locally. Therefore, it is recommended that the system be continuously developed, its features enhanced, and its online implementation be implemented immediately to provide broader benefits. This study aims to develop a website-based correspondence and complaint system accessible to the public and village officials. With this system, the public can submit letters and complaints digitally without having to visit the village office in person. This system also makes it easier for village officials to verify and document incoming complaints and letters in a more organized and efficient manner. The system development method used is the Waterfall method, which has clear and structured stages in each system development process. The results of this study indicate that the developed system successfully facilitates the digital submission of letters and complaints, which was previously done manually. The verification and documentation processes by village officials have also become more structured and efficient.